Trailblazing musical potential of the early lyrics of Paul Tychyna (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article discloses a trailblazing potential of pictorial means of musicality in the Ukrainian language. It explores the symbolism that provides a natural sound not directly motivated phonetic connection between music and the term laid the basis for the nomination convicing audible indication denotation (the motive): musical sound, rhythm, chord, instrument, melody, etc.
Keywords: graphic arts musicality; klarinets’; sound image; a musical term